The usage of taboo words and euphemism among Malaysian students on social media: a comparative Study / Ahmad Zahid Saidil Morsalin and Wardatul Hayat Adnan - Saidil Morsalin, Ahmad Zahid; Adnan, Wardatul Hayat (Universiti Teknologi MARA, 2022)
Social media has grown significantly and is familiar to Malaysian youth especially among the students. It is a platform for the students to communicate and reach others without barriers all around the world, specifically in Covid-19 pandemic situation. Reviewing the posting made by many Malaysian students on social media has alerted many of us to the use of taboo words (TW) and euphemisms (EM). Past research conducted showed that most college students use social media and spend many hours checking social media sites. Hence, it is important to review on the platforms used among these students. It is because the frequent use of TW is expected to lead to negative behavior and if EM has been chosen relatively, it will have led to good behavior. The present study focuses on the use of TW and EM words on Facebook, Twitter and Instagram posting made by Malaysian students. In addition, study has reported that communicating using impolite manners of ways used on social media has become a trend [1]. This situation is worrying as it contradicts Malaysian culture which promotes politeness. Therefore, the aims of the present study are to identify the use of TW and EM weightage in posting made through social media. Afterwards, comparative platforms will be reported to see the monopoly of using TW and EM through the three platforms namely (1) Facebook, (2) Twitter and (3) Instagram. To achieve this, qualitative study conducted through social media content and data collected from posting made by secondary students from the month of March 2020 - May 2020. Students were selected based on convenient sampling where most were closely related to researchers. The use of TW was used widely among students in Malaysia compared to EM.